Childhood epidermal necrolysis and erythema multiforme major: a multicentre French cohort study of 62 patients. (21st July 2021) - Giraud‐Kerleroux, L.; Bellon, N.; Welfringer‐Morin, A.; Leclerc‐Mercier, S.; Costedoat, I.; Coquin, J.; Brun, A.; Roguedas‐Contios, A.‐M.; Bernier, C.; Milpied, B.; Tétart, F.; Du Thanh, A.; et al.
Abstract: Introduction: The distinction between epidermal necrolysis [EN; including Stevens–Johnson syndrome (SJS), toxic epidermal necrolysis (TEN) and overlap syndrome] and erythema multiforme major (EMM) in children is confusing. We aimed to better describe and compare these entities. Materials and methods: This French retrospective multicentre study included children ≤18 years old referred for EN or EMM between 1 January 2008 and 1 March 2019. According to pictures, children were reclassified into TEN/overlap, SJS or EMM/unclassified (SJS/EMM) groups and compared for epidemiological and clinical data, triggers, histology and follow‐up. Results: We included 62 children [43 boys, median age 10 years (range 3–18)]: 16 with TEN/overlap, 11 SJS and 35 EMM. The main aetiologies were drugs in EN and infections (especially Mycoplasma pneumoniae ) in EMM ( P < 0.001), but 35% of cases remained idiopathic (TEN/overlap, 47%; SJS, 24%; EMM, 34%). The typical target lesions predominated in EMM ( P < 0.001), the trunk was more often affected in EN ( P < 0.001), and the body surface area involved was more extensive in EN ( P < 0.001). Mucosal involvement did not differ between the groups. Two patients with idiopathic TEN died. Histology of EMM and EN showed similar features. The recurrence rate was 42% with EMM, 7% with TEN/overlap and 0 with SJS ( P < 0.001). Sequelae occurred in 75% of EN but involved 55% of EMM. Conclusion: Clinical features of EN and EMM appeared well demarcated, with few overlapping cases. Idiopathic forms were frequent, especially for EN, meaning that a wide and thorough infectious screening, repeated if needed, is indicated for all paediatric cases of EN/EMM without any trigger drug. We propose a comprehensive panel of investigations which could be a standard work‐up in such situation. Sequelae affected both EN and EMM.